Report. The academic Information Schools network: Origins, evolution and future - Cobarsí-Morales, Josep (Anuario ThinkEPI, 2018)
The Information Schools (iSchools) are a prominent international academic network of information schools. Since its creation in 2005, about 80 universities have joined the network, through the respective faculties or departments thematically involved. The faculties or academic departments that are part of the iSchools study information, in close relationship with people and technology. We present a general overview of the iSchools that includes: the history of its origins and evolution, an updated review of its academic activity, and future trends. This overview is done through a critical review of a selection of existing literature on this academic movement. The review includes opinion and academic debate documents, scientific studies based on the collection and analysis of data from all the universities in the network or representative samples of them, and a look at the iConference, an annual world congress organized by this academic network.